Smart Tourism Development Post Earthquake and Covid 19 Pandemic in West Nusa Tenggara - Dewi Sartika Nasution; Naili Rahmawati (AIBPM Publisher, 2021)
One of the strategies that can be used to increase tourist visits after the earthquake disaster followed by the COVID-19 pandemic to West Nusa Tenggara is to utilize and apply information technology which is also known as the concept of smart tourism. This article aims to discuss smart tourism programs and applications in NTB. SWOT and Pest analysis method used to determine the relationship between external opportunities and internal strengths as well as internal weaknesses with external threats. Data was collected from interview with government tourism officer, observation and documentations. The results of the analysis can be used by the government or related parties in determining the direction of tourism development in NTB.